Improvements in the characterization of the efficiency degradation of water-to-water heat pumps under cyclic conditions. (1st October 2016) - Fuentes, E.; Waddicor, D.A.; Salom, J.
Highlights: Experimental characterization of a water-to-water heat pump at part load. High influence of inertia conditions on start-up losses of water-to-water heat pump. Assessment of the validity of parameterizations on efficiency loss at part load. New method for improved characterization of water-to-water heat pumps performance. Advice for improving the measurement of fixed-capacity heat pumps performance. Abstract: This paper presents a study on the characterization of the performance of a water-to-water heat pump of 40.5 kW fixed heating capacity under different cycling conditions scenarios. Semi-virtual laboratory experiments were conducted to analyse the influence of inertia from 1.23 to 24.7 L/kW on the efficiency of the heat pump operating at partial load. Different parameterizations in standards were compared to assess their ability to predict the energy efficiency degradation caused by cycling. Performance deterioration at part load was found to be highly dependent on inertia conditions, with non-negligible start-up parasitic effects detected for the heat pump under study, particularly for decreasing inertia. Results suggest that current standards for characterising the performance of systems at partial load, such as the European EN14825, should be reviewed to account for the influence of inertia on equipment performance and for the potential occurrence of start-up efficiency losses for water-to-water heat pumps. An expression is derived in this study for the start-up losses degradation coefficient C d and a single parameterization accounting for different sources of efficiency losses is proposed, together with a simple method to determine degradation coefficients from reduced experimentation.